The effectiveness of a brief home-based naturalistic language intervention on the spoken language abilities of children with autism in the Western Cape - Theron, Caroline (Division of Communication Sciences and Disorders, 2023)
Background: Naturalistic Developmental Behavioural Interventions (NDBIs) have shown to have a positive effect on cognitive and social outcomes of children with Autism Spectrum Disorder (ASD) though very few NDBIs have been implemented in low- and middle-income countries (LMIC). Challenges in accessing evidence-based interventions for many families of children with ASD living in LMIC exists due to the cost of travel, the remote locations of services, limited availability of services, and/or the financial implications thereof. Providing intervention in the child with ASD's home context may be one way for children to access intervention services needed. Enhanced Milieu Teaching (EMT) has shown to be effective in providing support to language development in children from LMIC. This study expands on previous research and literature by examining the effectiveness of clinician-implemented EMT when administered in the home context of children with ASD in low-resource settings in Cape Town, South Africa. Objectives: The study's objectives were to determine; i) Does the use of clinician implemented EMT within the home environment of children with ASD living with their families in the Metropolitan area of Cape Town, Western Cape increase the child's communication abilities, in particular the number of different words a child uses, ii) Do the communication gains made during the intervention generalise to the child's spoken language interactions with their primary caregivers? Methods: A single case study with multiple baseline design examined the effects of clinician-implemented home-based EMT intervention on the diversity and frequency of spoken language of young children with ASD in South Africa. Intervention sessions occurred in the homes of three young children with ASD between the ages of 45 and 72 months. Each participant presented with minimally verbal language abilities producing 1 word or less per minute at the start of the study, with an age equivalent of 20 months for their expressive language on the PLS-5. The participants received a minimum of 12 bi-weekly intervention sessions within their home context. Results: A 10-minute segment for each session was transcribed and coded using the Systematic Analysis of Language Transcripts (SALT; Miller & Chapman, 2008) using a prescribed EMT code. Results from the baseline and intervention sessions tracked the number of different words (NDW) used by the participants and was graphed to determine the effect of introducing the EMT intervention on the dependent variable. A functional relationship was demonstrated between the introduction of EMT and the increases in the NDW used for the three participants. The percentage of nonoverlapping data between the baseline and intervention sessions was above 92% for all participants. Evidence of generalisation of their spoken language abilities to interactions with their parents were observed. Conclusion: A functional relationship between the introduction of the EMT intervention and the increase in the participant's spoken language abilities indicated that EMT may be effective for improving spoken language skills of minimally verbal children with ASD when implemented in the home context by a trained clinician. Providing intervention services within a child with ASD's home context in South Africa is feasible and offers some relief from the logistical and financial strain placed on families of children with ASD in accessing services. The current findings may assist in determining ways to train parents in the implementation of EMT within their home context.